RESONANCES OF THE KNOWN IN THE UNKNOWN: Multifaith Spiritual Conversation - Barnes, Michael (The way, 2023)
The article discusses interfaith spiritual conversations and their implications.Topics include the importance of hospitality and respect in such conversations, the challenges of encountering the unknown, the need for active passivity and openness to divine grace, and the power of conversation as a tool for learning and understanding.